Pengaruh Terpaan dan Kualitas Informasi Akun Instagram @lrtjkt Terhadap Minat Beli Jasa - Fahmil Hakim; Dyah Anggraini (Fakultas Ekonomi dan Ilmu Sosial Program Studi Ilmu Komunikasi Universitas AMIKOM Yogyakarta, 2022)
The use of social media in public transportation services such as the LRT is one part of supporting the implementation of a smart city in Jakarta which is supported by sufficient information and technology. LRT Jakarta actively uses social media on the @lrtjkt instagram account as a form of encouraging the implementation of the smart city system in Jakarta. The purpose of this research was to see whether there was an influence of media exposure (X1) and the quality of information (X2) on the @lrtjkt instagram account on buying interest (Y) LRT Jakarta public transportation services. This research uses SOR (Stimulus-Organism-Response) theory with qualitative menthod with positivism paradigm. The data collection techique was carried out using a questionnaire method in the form of several statements which were then filled out by all respondents. The respondents in this research is followers of the instagram account @lrtjkt which were calculated using the Slovin formula so that a total sample is 400 respondents. The sample that will fill out the questionnaire is selected using the quota sampling technique. The results of the study show that media exposure and the quality of information on the @lrtjkt instagram account have a positive influence is 43.2% on buying interest LRT Jakarta public transportation services and remaining 56.8% is influenced by other factors outside the research. In the F-test, the calculated f-value is 152.867 > f-table 3.018 and the Sig. value is 0.000 < 0.05. While the T-test, the calculated t-value on the media exposure (X1) is 11.050 > t-table 1.966 and the Sig. value is 0.000 < 0.05 and the quality of information (X2) is 5.640 > t-table 1.966 and the Sig. value is 0.000 < 0.05. Based on these tests, it can be concluded that the overall hypothesis is stated that Ho is rejected and Ha is accepted.